Quantifying demands on the hamstrings during high-speed running: A systematic review and meta-analysis - Kemp, S.; Spence, A. L.; Keller, B. S.; Ducker, K. J.; Gucciardi, D. F. (Scandinavian Journal of Medicine & Science in Sports, 2023)
Introduction Hamstring strain injury (HSI) remains a performance, economic, and player availability burden in sport. High-speed running (HSR) is cited as a common mechanism for HSI. While evidence exists regarding the high physical demands on the hamstring muscles in HSR, meta-analytical synthesis of related activation and kinetic variables is lacking.